Meiotic studies in nine species of Erythrodiplax (Libellulidae, Odonata). Neo-XY sex chromosome system in E. media - Mola, L.M. (1996)
Erythrodiplax is an American genus of dragonflies with a mainly neotropical distribution and with 19 species cited in Argentine. In this work 9 species have been chromosomically analyzed: E. atroterminata, E. connata fusca, E. corallina, E. lygaea, E. media, E. melanorubra, E. nigricans, E. ochraceae and E. umbrata. All of them, except E. media, have n = 12 + X in males, with a similar karyotype and meiotic behaviour. Bivalents decrease gradually in size, except for the small m bivalent, whose size varies among the species. The X chromosome in E. corallina, E. lygaea, E. nigricans and E. umbrata is twice as large as in the other 4 species. On the other hand, E. media has n = 10 + neo-XY, m chromosomes, and its karyotype characterizes by the presence of two large bivalents (being the largest the heteromorphic neo-XY). The genus Erythrodiplax presents a great karyotypic constancy, although polytypisms for the m chromosome size have been detected in E. atroterminata, E. connata fusca and E. umbrata, and for the sex chromosome determining system, in E. media. The chromosome rearrangements that probably originated these polytypisms, and their evolutionary importance are discussed.